Endothelin B receptors contribute to retinal ganglion cell loss in a rat model of glaucoma. - Alena Z Minton; Nitasha R Phatak; Dorota L Stankowska; Shaoqing He; Hai-Ying Ma; Brett H Mueller; Ming Jiang; Robert Luedtke; Shaohua Yang; Colby Brownlee; Raghu R Krishnamoorthy (PLoS ONE, 2012)
Glaucoma is an optic neuropathy, commonly associated with elevated intraocular pressure (IOP) characterized by optic nerve degeneration, cupping of the optic disc, and loss of retinal ganglion cells which could lead to loss of vision. Endothelin-1 (ET-1) is a 21-amino acid vasoactive peptide that plays a key role in the pathogenesis of glaucoma; however, the receptors mediating these effects have not been defined. In the current study, endothelin B (ET(B)) receptor expression was assessed in vivo, in the Morrison's ocular hypertension model of glaucoma in rats. Elevation of IOP in Brown Norway rats produced increased expression of ET(B) receptors in the retina, mainly in retinal ganglion cells (RGCs), nerve fiber layer (NFL), and also in the inner plexiform layer (IPL) and inner nuclear layer (INL). To determine the role of ET(B) receptors in neurodegeneration, Wistar-Kyoto wild type (WT) and ET(B) receptor-deficient (KO) rats were subjected to retrograde labeling with Fluoro-Gold (FG), following which IOP was elevated in one eye while the contralateral eye served as control. IOP elevation for 4 weeks in WT rats caused an appreciable loss of RGCs, which was significantly attenuated in KO rats. In addition, degenerative changes in the optic nerve were greatly reduced in KO rats compared to those in WT rats. Taken together, elevated intraocular pressure mediated increase in ET(B) receptor expression and its activation may contribute to a decrease in RGC survival as seen in glaucoma. These findings raise the possibility of using endothelin receptor antagonists as neuroprotective agents for the treatment of glaucoma.